High strength rubberized concrete containing silica fume for the construction of sustainable road side barriers. (February 2015) - Elchalakani, Mohamed
Abstract: This paper provides strength and durability test results for rubberized concrete that contains silica fume (microsilica) for road side barriers with the intent to reduce injuries and fatalities during crashes. The test program involved the preparation of normal and high strength concretes made out of recycled waste tire rubber. The high strength was obtained by adding silica fume which enhanced the interfacial transition zone bonding. Tire rubber particles composed of a combination of crumb rubber and fine rubber powder were used to replace 10%, 20%, 30%, and 40%, of the total weight of the fine mineral aggregate. The fresh rubberized concrete exhibited lower unit weight and acceptable workability compared to plain concrete. The results of the uniaxial compressive and flexural tests conducted on hardened concrete specimens indicated considerable reductions in axial strength, flexural strength, and tangential modulus of elasticity. Cube Drop tests were performed and showed good resilience of the rubberized concrete. New design guidelines in accordance with the Australian Bridge Design Code AS 5100 for strength and serviceability of rubberized concrete road side barriers were derived based on the test results. New moment–thrust interaction curves and shear strength equations were derived for the rubberized concrete road side barriers. The newly derived design rules showed that shear strength is critical compared to the combined moment and axial thrust and the maximum rubber contents were 17% and 30% for normal and high strength concretes, respectively.